Catching the wind : Penang in a rising - Hutchinson, Francis E.; Saravanamuttu, Johan (Singapore : Institute of Southeast Asian Studies, 2012)
However impressive the economic success of Penang has been over the past four decades, structural conditions in the region call for a fundamental reconfiguration of this Malaysian state's competitive advantage. In the 1970s, the ageing entrepot transformed itself into a manufacturing hub for the electronics industry and a well-known tourist site. This outward-looking model of economic growth has underpinned Penang's economic development up until the present. The question that now arises is whether Penang's present mode of development will continue to be effective, or whether it will have to try.
Includes bibliographical references
Keywords: Investments, Foreign -- Pinang; Pinang -- Economic conditions; Pinang -- Economic policy; Pinang -- History; Pinang -- Social life and customs; World Heritage areas -- Malaysia -- Pinang